A Middle Dorset semi-subterranean dwelling at Point Riche, Newfoundland - Eastaugh, Edward (Études/Inuit/Studies)

(untitled) (Association Inuksiutiit Katimajiit Inc., 2003)
AbstractThis paper presents the findings of archaeological investigations at the Middle Dorset site EeBi-20 at Point Riche, Newfoundland. The site consists of approximately 17 semi-subterranean house depressions dispersed for 150 meters along a raised terrace 10 meters above sea level. It is interpreted as a spring base camp, positioned to take advantage of the large harp seal herds that migrate past the site between March and early June. Excavations during 2001 revealed the remains of a well-preserved dwelling (House Feature 30) consisting of an earth and stone platform surrounding a central depression. A cobble axial feature that incorporated a large limestone slab divides the dwelling. A number of external features are associated with the dwelling including two hearths, a "pot-stand" and numerous artifact clusters representing distinct activity areas. A single radiocarbon date of 1650 ± 40 B.P. (uncalibrated, Beta-160980) was obtained from the occupation deposit found on the house floor.